The Effect of Transformational Leadership on the Performance of Employees With Affective Commitment as a Mediation Variable at the Salapian Sub-district Office, Langkat Regency - Sugiono; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of transformational leadership on Employee Performance mediated by affective commitment at the Salapian Sub-district Office. This research was conducted with a causal associative quantitative approach. The sample used was all employees of the company, with a total of 50 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that transformational leadership has a positive and significant effect on employee performance. This can be seen from the T-statistical value of 5.312 < 1.96. Transformational leadership also has a positive and significant effect on affective commitment, the T-Statistical value data obtained is 69.760 > 1.96. Likewise, affective commitment has a positive and significant influence on Employee performance with a T-Statistic value of 9.332 > 1.96. Meanwhile, in the results of indirect influence, it was explained that affective commitment was able to significantly intervene in the influence of transformational leadership on Employee Performance with the results of T-Statistics of 8.974 > 1.96 with a P-Value of 0.000 < 0.05. This identifies that Meaning, improvements in transformational Leadership can contribute to an increase in affective Commitment, which in turn has an impact on improving Employee performance